Peripheral arterial disease and type 2 diabetes: Older patients still exhibit a survival benefit from glucose control. (April 2020) - Höbaus, Clemens; Herz, Carsten Thilo; Wrba, Thomas; Koppensteiner, Renate; Schernthaner, Gerit-Holger
Objective: To investigate a possible beneficial effect of strict glycaemic control on all-cause mortality in patients with peripheral arterial disease and type 2 diabetes mellitus. Methods: A total of 367 mainly older peripheral arterial disease patients [age: 69 (62–78) years, 34% women, Fontaine stage I–II] were categorized according to glycaemic control, that is, (a) no type 2 diabetes mellitus, (b) strict glucose control (HbA1c < 53 mmol/mol) and (c) lenient glucose control (HbA1c ⩾ 53 mmol/mol) at inclusion and by mean HbA1c over the first study year. Mortality was analysed using Kaplan–Meier and Cox-regression analyses after 7 years. Results: The combination of type 2 diabetes mellitus and peripheral arterial disease reduced survival from 78.8% to 68.9% in comparison to patients without type 2 diabetes mellitus ( p = 0.023). Patients with strict glucose control (75%) were associated with increased survival in comparison to patients with lenient glucose control (58.9%) stratified by mean HbA1c ( p = 0.042). Baseline cardiovascular risk factors were similar in those type 2 diabetes mellitus patients. In this peripheral arterial disease cohort HbA1c (hazard ratio: 1.3, 1.04–1.63), age (hazard ratio: 1.7, 1.3–2.3) and C-reactive protein (hazard ratio: 1.5, 1.2–2.0) remained independent associates for mortality adjusted for cardiovascular risk factors and diabetes duration. Conclusion: Older patients with peripheral arterial disease and type 2 diabetes mellitus still benefit from strict glucose control in a cohort of patients with similar distribution of cardiovascular risk factors.